Credit risks as a key component of a bank's risk management system - Cui Quanlin (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
Object of research is the banking system of China. Subject of researchThe theoretical basis of bank credit risk management in the context of sustainable and effective risk management operations. Purpose of qualification master'swork As a key component of bank risk management system, credit risk is crucial to global financial stability and bank operation. Although significant progress has been made at the international level, the field still faces many challenges, especially in the assessment and control of credit risk. The purpose of this study is to systematically explore the credit risk management of China's banking industry, and analyze its theoretical basis, current system and future development path. According to results of the research, The results show that China has accumulated rich experience in credit risk management, but it still needs to be further optimized to cope with the changing market environment. The obtained results can be used This study not only provides a new theoretical perspective for the academic community, but also provides practical guidance for policy makers and bankers. The final conclusion emphasizes that continuous attention to the development of credit risk management is of great significance to ensure the sound operation of the financial system.
Кредитні ризики як ключова складова системи ризик-менеджменту банку
Scientific advisor: Kochorba Valeriia, PhD of economics, associate professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; credit risk; banking; risk management; china's financial system; sustainable development